MODEL PERLINDUNGAN HUKUM INTEGRATIF BURUH MIGRAN INDONESIA DALAM MASYARAKAT EKONOMI ASEAN - Abdul Rasyid Saliman; E. Vita Mutiarawati (PROGRESIF: Jurnal Hukum, 2016)
The effort of providing protection for all Indonesian migrant workers abroad is focused on two categories. Firstly, the phase of pre-departure of Indonesian migrant workers in which an approach of cross sectors is carried out by both the Indonesian government and the private agencies in order to prepare them with all the things needed when they arrive at countries of their destination. Secondly is the phase of arrival and post-arrival of Indonesian migrant workers abroad. As in Malaysia, the policy on the arragenment of labor affairs either for Malaysian workers or for foreign workers is officially and legally protected in Labor Act of 1955, Industrial Relation Act of 1967, Trade Union Act of 1959, and in Compensation Act of 1952. The process of labor trials is settled through The Labor Court. This Labor Court no more handles the process of trial of illegally foreign workers. There are needs of establishing Labor Cooperation Agreement (LCA) on the ministerail level, Implementaion Agreement serving as the general policy on the executors level as well as Standardized Labor Contract which has been amended. The establishments of Labor Cooperation Agreement, Implementing Agreement and Standardized Labor Contract should occur before all workers leave Indonesia and are aimed at providing legal protection for every single Indonesian migrant worker. In order that there is no collision between the Malaysian laws and Indonesian laws, the government officials of related issues of both countries must do observations and conduct discussions without neglecting the prevail laws of each country. Any issue of labor affairs should always be referred to the laws of both countries.